Polyamide composition and preparation method thereof

By melt blending PA66 slices with black phosphorus, carbon nanotubes, additives and stearamide fatty acids, a polyamide composition with excellent flame retardant and antistatic properties was prepared, and the production of PA66 polyamide during friction was solved. Sparks and fire problems and improves the heat resistance and mechanical strength of the material.

CN117887252BActive Publication Date: 2025-02-18HUNAN XINJIYUAN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410059807.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-02-18
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

PA66 polyamide generates charge during friction, causing sparks and fires, and its covalent bond breaks in the flame to trigger a chain combustion reaction, resulting in a fire. At the same time, adding flame retardant will reduce the mechanical properties of the material.

Method used

Polyamide compositions with excellent flame retardant and antistatic properties were prepared by melt blending PA66 slices with black phosphorus, carbon nanotubes, additives and stearamide fatty acids. Black phosphorus provides flame retardant effects, carbon nanotubes provide conductivity, additives and stearamide fatty acids ensure uniform dispersion and improved performance of the material.

Benefits of technology

The obtained polyamide composition has stable and efficient flame retardant and antistatic properties, and has certain heat resistance and mechanical strength, and is suitable for textile fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004666033560000021
    Figure BDA0004666033560000021
  • Figure BDA0004666033560000031
    Figure BDA0004666033560000031
  • Figure BDA0004666033560000032
    Figure BDA0004666033560000032
Patent Text Reader

Abstract

The invention discloses a polyamide composition and a preparation method thereof, and belongs to the technical field of polyamide compositions. It is prepared by melt blending PA66 slices, black phosphorus, additives, carbon nanotubes, and stearamide fatty acids in a mass ratio of 84:4:5-15:5:2. PA66 is the main body, with good heat resistance, high mechanical strength, and excellent comprehensive performance; black phosphorus has an excellent flame retardant effect, and can synergize with the additives to jointly enhance the flame retardancy of the polyamide composition; carbon nanotubes have electrical conductivity, giving the polyamide composition antistatic properties; stearamide fatty acids can make black phosphorus and carbon nanotubes evenly dispersed in the polyamide combination, and better exert performance; in addition, the additives can significantly improve the flame retardancy and antistatic properties of the polyamide composition. The polyamide composition thus obtained has stable and efficient flame retardancy and antistatic properties, and has certain heat resistance and mechanical strength, and has important application significance in the field of textiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polyamide compositions, and in particular, relates to a polyamide composition and a preparation method thereof. Background Art

[0002] Polyamide, commonly known as nylon, was initially used as a raw material for spinning. Due to its outstanding characteristics such as strong tensile strength, good abrasion resistance, strong corrosion resistance and fatigue resistance, it has developed rapidly in recent years and has been widely used in many industrial fields such as chemical fiber textiles, transportation, electronic appliances and construction. It is an important part of today's new materials industry. PA66 occupies a dominant position in polyamide due to its excellent comprehensive performance. However, with the continuous expansion of market demand, the shortcomings of PA66 have also been exposed. Due to the insulation of the PA66-based material itself, the charge generated during the friction process cannot be transmitted in time. The charge accumulated on the surface will break through the air insulation, generate sparks, and ignite itself or surrounding combustibles to form a fire source. At the same time, because its internal part exists in the form of covalent bonds with weaker bond energy, when it is burned by flames to obtain energy, these covalent bonds will break to generate free radicals, triggering a chain combustion reaction. The polymer will continue to burn, thus causing a fire. Therefore, it is very important to improve the flame retardant and antistatic properties of PA66.

[0003] At present, the main method is to add flame retardant and antistatic fillers. However, there is little research on improving the flame retardancy and antistatic properties of PA66 at the same time. Some commonly used flame retardants are added in large amounts. Excessive addition will lead to reduced mechanical properties of PA66 materials, limiting its application areas. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a polyamide composition and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a polyamide composition comprises the following steps:

[0007] PA66 chips, black phosphorus (BP), additives, carbon nanotubes and stearamide fatty acid (dispersant) are mixed, added into a twin-screw extruder, melt-blended, and extruded to obtain a polyamide composition.

[0008] PA66 is selected as the main body, which has good heat resistance, high mechanical strength and excellent comprehensive performance. In addition, black phosphorus, as an emerging two-dimensional material, has excellent flame retardant effect in addition to characteristic size effect and thermal stability, and can work synergistically with additives to enhance the flame retardancy of the polyamide composition. In addition, carbon nanotubes themselves have good electrical conductivity, giving the polyamide composition excellent antistatic properties. Finally, stearamide fatty acid can make black phosphorus and carbon nanotubes evenly dispersed in the polyamide combination, so as to better perform their performance.

[0009] Furthermore, the mass ratio of the PA66 slices, black phosphorus, additives, carbon nanotubes, and stearylamide fatty acid is 84:4:5-15:5:2.

[0010] Furthermore, the auxiliary agent is prepared by the following steps:

[0011] S1. Add 2,3-butanediol, ethanol and triethylamine (remove the generated hydrogen chloride) into a three-necked flask and mix well. Add acetyl chloride dropwise and stir for 40 min. After the reaction is completed, first remove part of the solvent by rotary evaporation, then purify by column chromatography (the eluent is a mixed solvent of methanol / ethyl acetate, and the volume ratio of the two is 1:8), and finally remove the eluent by rotary evaporation to obtain intermediate 1; the ratio of 2,3-butanediol, ethanol, triethylamine and acetyl chloride is 10.2 g:50 mL:50 mL:7.8 g;

[0012] 2,3-Butanediol and acetyl chloride undergo esterification reaction to protect one hydroxyl group. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of 2,3-butanediol, only one -OH on 2,3-butanediol participates in the reaction to obtain intermediate 1. The specific reaction process is shown below:

[0013]

[0014] S2, in a three-necked flask equipped with a stirring reflux device, intermediate 1, chloroform, triethylamine (removing the generated hydrogen chloride), and dichloromethyl phosphine were mixed and stirred evenly, then slowly heated to 80 ° C, refluxed for 4 hours, the reaction was completed, unreacted dichloromethyl phosphine and solvent were removed under reduced pressure, water was added to mix, and intermediate 2 was obtained by extraction with ethyl acetate; the ratio of the amount of intermediate 1, chloroform, triethylamine, and dichloromethyl phosphine was 13.2g:50mL:50mL:15.4g;

[0015] Dichloromethylphosphine reacts with intermediate 1 to undergo an esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the dichloromethylphosphine to be slightly excessive, only one -Cl on the dichloromethylphosphine participates in the reaction to obtain intermediate 2. The specific reaction process is shown below:

[0016]

[0017] S3. At room temperature and under nitrogen protection, add intermediate 2, 2-amino-4-mercaptobutyric acid and DMSO (dimethyl sulfoxide) to a three-necked flask equipped with a stirring and reflux device, mix, stir evenly, slowly heat to 70°C, react for 6 hours, stop heating, wait for the temperature in the reaction flask to drop to 30°C, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of pyridine / benzene, the volume ratio of the two is 4:3), and finally remove the eluent by rotary evaporation to obtain intermediate 3; the ratio of intermediate 2, 2-amino-4-mercaptobutyric acid and DMSO is 22.8g:13.5g:100mL;

[0018] Intermediate 2 and 2-amino-4-mercaptobutyric acid undergo acylation reaction to obtain intermediate 3; the specific reaction process is as follows:

[0019]

[0020] S4. Add intermediate 3, AIBN (azobisisobutyronitrile) and DMSO into a three-necked flask, mix and stir evenly, then drop allyl polyoxyethylene ether (relative molecular weight 1200), maintain the temperature of the system at 80°C, react for 4 hours, and after the reaction, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / ether, and the volume ratio of the two is 2:3), and remove the eluent by rotary evaporation to obtain intermediate 4; the ratio of the amount of intermediate 3, AIBN, DMSO, and allyl polyoxyethylene ether is 3.2g:0.2g:50mL:12g;

[0021] Under the action of AIBN, the unsaturated carbon-carbon double bond on the allyl polyoxyethylene ether molecule undergoes a thiol-ene click reaction with the -SH on the intermediate 4 to obtain the intermediate 4. The specific reaction process is as follows:

[0022]

[0023] S5. Add melamine, intermediate 4 and DMSO to a three-necked flask equipped with a stirring device, mix and stir evenly, add DCC (dicyclohexylcarbodiimide, dehydrating agent), react for 3 h in a water bath at 50°C, add NaOH solution (mass fraction 12%), react for 1 h at 75°C, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / methanol, the volume ratio of the two is 3:5), remove the eluent by rotary evaporation to obtain an auxiliary agent; the ratio of melamine, intermediate 4, DMSO, DCC and NaOH solution is 12.6 g:138.7 g:300 mL:61.8 g:100 mL;

[0024] The amino group of melamine reacts with the carboxyl group of intermediate 4 to undergo amidation reaction. By controlling the molar ratio of the two to be close to 1:3 and the excess of intermediate 4, the three -NH 2 It can fully react. The electrophilicity of amino group is stronger than that of hydroxyl group. With the help of dehydrating agent, it can react under mild conditions. NaOH solution provides alkaline environment, hydrolysis occurs, and auxiliary agent is obtained. The specific reaction process is as follows:

[0025]

[0026] The obtained auxiliary agent contains amide groups, hydrophilic chain polyethylene glycol, hydroxyl groups, and PN flame retardant components, wherein the amide groups can increase the compatibility of the auxiliary agent with the polyamide composition, so that the performance of the auxiliary agent can be fully exerted; secondly, the hydrophilic chain polyethylene glycol has excellent hydrophilicity. When it is used in the field of textiles, the higher the hydrophilicity, the better the antistatic performance, so the polyamide composition can be given extremely strong antistatic performance. Moreover, the unreacted hydroxyl groups can further enhance the hydrophilicity and antistatic performance of the polyamide composition. In addition, the amide group and the hydroxyl group have obvious polar effects and are easy to form hydrogen bonds with the surrounding H atoms, further enhancing the compatibility of the auxiliary agent with the polyamide composition and the stability of the auxiliary agent molecules themselves; in addition, the PN flame retardant component is a halogen-free flame retardant, which has a high decomposition temperature and good thermal stability, and at the same time has the synergistic flame retardant effect of phosphorus-based and nitrogen-based flame retardants, and can give the polyamide composition safe and efficient flame retardant performance.

[0027] Beneficial effects of the present invention:

[0028] The polyamide composition obtained by the present invention is prepared by melt blending of PA66 slices, black phosphorus, additives, and carbon nanotubes. PA66 is selected as the main body, and has good heat resistance, high mechanical strength, and excellent comprehensive performance; black phosphorus has good thermal stability, and also has excellent flame retardant effect, and can synergize with the additives to jointly enhance the flame retardancy of the polyamide composition; carbon nanotubes themselves have good electrical conductivity, giving the polyamide composition excellent antistatic properties; stearamide fatty acids can make black phosphorus and carbon nanotubes evenly dispersed in the polyamide combination, and better exert their performance; in addition, the added additives contain various functional groups, which significantly improve the flame retardancy, antistatic and hydrophilicity of the polyamide composition. Therefore, the polyamide composition obtained has stable and efficient flame retardancy and antistatic properties, and has certain heat resistance and mechanical strength, and has important application significance in the field of textiles. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] Preparation aids:

[0032] S1. Add 10.2 g of 2,3-butanediol, 50 mL of ethanol and 50 mL of triethylamine into a three-necked flask and mix well. Add 7.8 g of acetyl chloride dropwise and stir for 40 min. After the reaction is completed, first remove part of the solvent by rotary evaporation, then purify by column chromatography (the eluent is a mixed solvent of methanol / ethyl acetate, and the volume ratio of the two is 1:8), and finally remove the eluent by rotary evaporation to obtain intermediate 1;

[0033] S2, in a three-necked flask equipped with a stirring reflux device, 13.2 g of intermediate 1, 50 mL of chloroform, 50 mL of triethylamine, and 15.4 g of dichloromethylphosphine were mixed and stirred evenly, then the temperature was slowly raised to 80° C., and refluxed for 4 h. After the reaction was completed, unreacted dichloromethylphosphine and solvent were evaporated under reduced pressure, water was added to mix, and the mixture was extracted with ethyl acetate to obtain intermediate 2;

[0034] S3, at room temperature and under nitrogen protection, in a three-necked flask equipped with a stirring and reflux device, add 22.8 g of intermediate 2, 13.5 g of 2-amino-4-mercaptobutyric acid and 100 mL of DMSO, mix, stir evenly, slowly heat to 70 ° C, react for 6 hours, stop heating, wait for the temperature in the reaction bottle to drop to 30 ° C, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of pyridine / benzene, the volume ratio of the two is 4:3), and finally remove the eluent by rotary evaporation to obtain intermediate 3;

[0035] S4, add 3.2g of intermediate 3, 0.2g of AIBN and 50mL of DMSO into a three-necked flask, mix and stir evenly, then drop 12g of allyl polyoxyethylene ether (relative molecular weight 1200), maintain the temperature of the system at 80°C, react for 4h, after the reaction is completed, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / ether, the volume ratio of the two is 2:3), and remove the eluent by rotary evaporation to obtain intermediate 4;

[0036] S5. Add 12.6 g of melamine, 138.7 g of intermediate 4 and 300 mL of DMSO to a three-necked flask equipped with a stirring device, mix and stir evenly, add 61.8 g of DCC, react in a water bath at 50°C for 3 h, add 100 mL of NaOH solution (mass fraction 12%), react at 75°C for 1 h, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / methanol, the volume ratio of the two is 3:5), remove the eluent by rotary evaporation to obtain an auxiliary agent.

[0037] Example 2

[0038] Preparation aids:

[0039] S1. Add 20.4 g of 2,3-butanediol, 50 mL of ethanol and 50 mL of triethylamine into a three-necked flask and mix well. Add 15.6 g of acetyl chloride dropwise and stir for 40 min. After the reaction is completed, first remove part of the solvent by rotary evaporation, then purify by column chromatography (the eluent is a mixed solvent of methanol / ethyl acetate, and the volume ratio of the two is 1:8), and finally remove the eluent by rotary evaporation to obtain intermediate 1;

[0040] S2, in a three-necked flask equipped with a stirring reflux device, 26.4 g of intermediate 1, 100 mL of chloroform, 100 mL of triethylamine, and 30.8 g of dichloromethylphosphine were mixed and stirred evenly, then slowly heated to 80° C., refluxed for 4 h, and after the reaction was completed, unreacted dichloromethylphosphine and solvent were evaporated under reduced pressure, water was added to mix, and the mixture was extracted with ethyl acetate to obtain intermediate 2;

[0041] S3, at room temperature and under nitrogen protection, in a three-necked flask equipped with a stirring and reflux device, add 45.6 g of intermediate 2, 27.0 g of 2-amino-4-mercaptobutyric acid and 200 mL of DMSO, mix, stir evenly, slowly heat to 70 ° C, react for 6 hours, stop heating, wait for the temperature in the reaction bottle to drop to 30 ° C, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of pyridine / benzene, the volume ratio of the two is 4:3), and finally remove the eluent by rotary evaporation to obtain intermediate 3;

[0042] S4, add 6.4g of intermediate 3, 0.4g of AIBN and 50mL of DMSO into a three-necked flask, mix and stir evenly, then add 24g of allyl polyoxyethylene ether (relative molecular weight 1200) dropwise, maintain the temperature of the system at 80°C, react for 4h, after the reaction is completed, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / ether, the volume ratio of the two is 2:3), and remove the eluent by rotary evaporation to obtain intermediate 4;

[0043] S5. Add 25.2 g of melamine, 277.4 g of intermediate 4 and 600 mL of DMSO to a three-necked flask equipped with a stirring device, mix and stir evenly, add 123.6 g of DCC, react in a water bath at 50°C for 3 h, add 200 mL of NaOH solution (mass fraction 12%), react at 75°C for 1 h, first remove part of the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of ethyl acetate / methanol, the volume ratio of the two is 3:5), remove the eluent by rotary evaporation to obtain an auxiliary agent.

[0044] Example 3

[0045] 84 g of PA66 chips, 4 g of black phosphorus (BP), 5 g of the additive prepared in Example 1, 5 g of carbon nanotubes and 2 g of stearamide fatty acid (dispersant) were mixed and added to a twin-screw extruder, melt blended and extruded to obtain a polyamide composition, which was melt-spun to make a polyamide fiber fabric.

[0046] Example 4

[0047] 84 g of PA66 chips, 4 g of black phosphorus (BP), 10 g of the additive prepared in Example 1, 5 g of carbon nanotubes and 2 g of stearamide fatty acid (dispersant) were mixed and added to a twin-screw extruder, melt blended and extruded to obtain a polyamide composition, which was melt-spun to make a polyamide fiber fabric.

[0048] Example 5

[0049] 84 g of PA66 chips, 4 g of black phosphorus (BP), 15 g of the additive prepared in Example 2, 5 g of carbon nanotubes and 2 g of stearamide fatty acid (dispersant) were mixed and added to a twin-screw extruder, melt blended and extruded to obtain a polyamide composition, which was melt-spun to make a polyamide fiber fabric.

[0050] Comparative Example 1

[0051] PA antistatic agent of equal quality produced by Shandong Juli Antistatic Technology Co., Ltd. was used to replace the auxiliary agent in Example 5, and the remaining steps were the same as in Example 5.

[0052] Comparative Example 2

[0053] PA flame retardant of equal quality produced by Shanghai Xinglong Technology Co., Ltd. was used to replace the auxiliary agent in Example 5, and the remaining steps were the same as in Example 5.

[0054] Comparative Example 3

[0055] Use ordinary PA66.

[0056] The polyamide fibers obtained in Examples 3-5 and Comparative Examples 1-3 were made into corresponding shapes according to different test standards and subjected to the following performance tests:

[0057] The limiting oxygen index was determined using the national standard GB / T 2406-2008 "Test method for combustion performance of plastics";

[0058] The specific resistance is measured using the national standard GB / T 14342-1993 "Test method for specific resistance of synthetic staple fibers";

[0059] The electrostatic half-life was determined using FZ / T 01042-1996 "Determination of electrostatic voltage half-life for electrostatic properties of textile materials";

[0060] The national standard GB / T 1040-92 "Test method for tensile properties of plastics" is used to measure the tensile strength of the sample at room temperature, recorded as F1, and the tensile strength is recorded as F2 when placed at 200℃ for 12 hours;

[0061] The test results are shown in the following table:

[0062]

[0063] It can be seen from the above table that the obtained polyamide composition has stable and efficient flame retardancy and antistatic properties, and has certain heat resistance and mechanical strength, and has important application significance in the field of textiles.

[0064] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0065] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a polyamide composition, characterized in that: The following steps are involved: PA66 chips, black phosphorus, additives, carbon nanotubes and stearamide fatty acid were mixed, magnetically stirred for 2 hours, placed in a 60° C. water bath for 2 hours, and melt-blended and extruded in a twin-screw extruder to obtain a polyamide composition; Wherein, the auxiliary agent is prepared by the following steps: S1. Mix 2,3-butanediol, ethanol and triethylamine, add acetyl chloride dropwise, stir for 40 min, rotary evaporate, purify by column chromatography, and rotary evaporate again to obtain intermediate 1; the ratio of 2,3-butanediol, ethanol, triethylamine and acetyl chloride is 10.2 g:50 mL:50 mL:7.8 g; S2, intermediate 1, chloroform, triethylamine, and dichloromethylphosphine were mixed, stirred evenly, refluxed at 80°C for 4h, distilled under reduced pressure, mixed with water, and extracted with ethyl acetate to obtain intermediate 2; the ratio of intermediate 1, chloroform, triethylamine, and dichloromethylphosphine was 13.2g:50mL:50mL:15.4g; S3. Under nitrogen protection, the intermediate 2, 2-amino-4-mercaptobutyric acid and dimethyl sulfoxide (DMSO) were mixed, stirred evenly, reacted at 70°C for 6h, rotary evaporated, purified by column chromatography, and rotary evaporated again to obtain intermediate 3; the ratio of intermediate 2, 2-amino-4-mercaptobutyric acid and dimethyl sulfoxide (DMSO) was 22.8g:13.5g:100mL; S4, the intermediate 3, azobisisobutyronitrile AIBN and dimethyl sulfoxide DMSO were mixed, allyl polyoxyethylene ether was added dropwise, the reaction was carried out at 80°C for 4h, rotary evaporation was performed, column chromatography was used for purification, and rotary evaporation was performed again to obtain intermediate 4; the relative molecular mass of allyl polyoxyethylene ether was 1200, and the usage ratio of intermediate 3, azobisisobutyronitrile AIBN, dimethyl sulfoxide DMSO and allyl polyoxyethylene ether was 3.2g:0.2g:50mL:12g; S5. Mix melamine, intermediate 4 and dimethyl sulfoxide (DMSO), add dicyclohexylcarbodiimide (DCC), react at 50°C for 3 h, add sodium hydroxide (NaOH) solution, react at 75°C for 1 h, rotary evaporation, purify by column chromatography, and rotary evaporation again to obtain an auxiliary agent; the dosage ratio of melamine, intermediate 4, dimethyl sulfoxide (DMSO), dicyclohexylcarbodiimide (DCC) and sodium hydroxide (NaOH) solution is 12.6 g: 138.7 g: 300 mL: 61.8 g: 100 mL.

2. The method for preparing a polyamide composition according to claim 1, characterized in that: The mass ratio of the PA66 slices, black phosphorus, additives, carbon nanotubes and stearylamide fatty acid is 84:4:5-15:5:

2.

3. A polyamide composition, characterized in that Prepared according to the method according to any one of claims 1-2.

Citation Information

Patent Citations

  • Method for preparing functional polyamide fiber

    CN102719929A

  • Antistatic, halogen-free, and fire-retardant enhanced master batch dedicated for polyamide and preparation method thereof

    CN103351618A